Pelatihan Aplikasi Pembangkit Listrik Tenaga Bayu (PLTB) untuk Lampu Taman di Sekolah SMAN 57 Jakarta - Ibnu Hajar; Edi Ispranyoto; Albert Gifson; Juara Mangapul Tambunan (Terang, 2018)
This community services (Pengabdian Kepada Masyarakat / P2M) workshop is lecturers and university students activity for renewable energy (Energi Baru dan Terbarukan / EBT) application. This activity is initiated by lecturers of Collage of Engineering of PLN to implemented their knowledge in Electrical Engineering field to train students from senior high school level, especially in sharing knowledge about science application that many used recently in remote areas of Indonesia that is public lighting “Workshop of Wind Power Plant Application for Garden Lamp” on School of SMAN 57 Jakarta, located in Kedoya Utara, Kebun Jeruk, Kodya Jakarta Barat, DKI Jakarta.Authors in Community Services team choosed workshop of this application of “Wind Power Plant for Garden Lamp is to give explanation about how to build design, work function and its benefit in people life in general and school in particular.In the design, material choosing of blade that can made from wood or alluminium, choosed based on wind speed characteristic and it did testing of influenced material to blade rotating power speed. Potency of wind energy in Indonesia have been identificated at many kind of area especially in Java, South Celebes, South East Nusa and Maluku.Through the workshop of wind power plant application for garden lamp used, is one of the program that be developed by lecturers and students of Collage of Engineering of PLN, and the result of this workshop developing be given for free of charge for school of SMAN 57 Jakarta students, for sciences that got in teory from lesson school can be implemented on practices.